Gli ‘spazi’ della politica - Cotroneo, Girolamo (Filosofia, 2016)
This essay considers political space within Hannah Arendt’s work, with a focus on her interpretation of the Greek polis’ democratic experience. Starting from an analysis of space intended both literally and figuratively, this essay concludes with an interpretation of Arendt’s philosophy as a problematisation of the relationship between political freedom and the twentieth-century totalitarian regimes.